Living Up to a Name: Gender Role Behavior Varies With Forename Gender Typicality - Alexander, Gerianne M.; John, Kendall; Hammond, Tracy; Lahey, Joanna (Frontiers in Psychology, 2021)
Forenames serve as proxies for gender labels that activate gender stereotypes and gender socialization. Unlike rigid binary gender categories, they differ in the degree to which they are perceived as “masculine” or “feminine”. We examined the novel hypothesis that the ability of a forename to signal gender is associated with gender role behavior in women (n=215) and men (n=127) (M=19.32, SD=2.11) as part of a larger study evaluating forenames used in resume research. Compared to individuals endorsing a “gender-strong” forename, those perceiving their forename as relatively “gender-weak” reported less gender-typical childhood social behavior and a weaker expression of gender-linked personality traits. Our findings suggest that forenames strengthen or weaken gender socialization, gender identification, and so contribute to the variable expression of gender role behavior within binary gender groups.